Iseljenice/povratnice u 21. stoljeću - percepcija povratka u Hrvatsku - Mesarić Žabčić, Rebeka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
This paper is based on the migration experience of five female migrants/returnees from different Croatian regions. During their migration process they were at the same time on the individual, family and social level involved in the process of migration as in model of social network theory. According to this theory migrants use common networks of interests that span over national borders. The paper will show how preparedness for return depends not only on the intention and desire to return to their country of origin, but depends on the individuals current and actual readiness. Except migration experiences, the degree of readiness to return also depends on the migrants perception of institutional, political and economic trends in the country of origin. A positive impacton the homeland will occur only when the return is realized in the moment that is optimal for the individuals return. By using the oral history method, the hypothesis that a high degree of readiness determines the optimal return is confirmed.
Keywords: izseljenstvo; zunanje migracije; povratne migracije; woman; ženske; podjetništvo